Biometrics of wild Red-breasted Geese Branta ruficollis - Mitchell, Carl; Cranswick, Peter; Kharitonov, Sergei; Mitev, Daniel; Quinn, John L.; Rozenfeld, Sonia; Swann, Bob; Vangeluwe, Didier (Wildfowl, 2015)
Biometrics were taken from 242 Red-breasted Geese Branta ruficollis caught in summer on the Taimyr, Yamal and Gydan Peninsulas, arctic Russia in 1996 and 2007–2014, and from 94 birds during four catches on the wintering grounds in Bulgaria in 2011–2014. These biometrics represent the first published data of body measurements, flat wing lengths and mass for Red-breasted Geese using sample sizes of more than 14 birds. Males were larger than females amongst adults and first-winter birds. Adult male body mass was lower in winter than during moult, whereas females showed no significant difference. In common with some other arctic-moulting goose species, the mass of most adult geese remained constant throughout the flightless moult period; however, the mass of non-breeding adult females declined. An index of adult winter flat wing length x body mass was a 100% accurate predictor of sex determined by cloacal eversion (n = 22), but was less successful in determining the sex of first-winter birds (92–93%, n = 27).